2022
DOI: 10.1038/s41598-022-11159-y
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an elusive spliceogenic MYBPC3 variant in an otherwise genotype-negative hypertrophic cardiomyopathy pedigree

Abstract: The finding of a genotype-negative hypertrophic cardiomyopathy (HCM) pedigree with several affected members indicating a familial origin of the disease has driven this study to discover causative gene variants. Genetic testing of the proband and subsequent family screening revealed the presence of a rare variant in the MYBPC3 gene, c.3331−26T>G in intron 30, with evidence supporting cosegregation with the disease in the family. An analysis of potential splice-altering activity using several splicing algorit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 58 publications
(58 reference statements)
0
9
0
Order By: Relevance
“…Around 75% of these variants were found to be loss-of-function and resulted in absent or truncated proteins with impaired ability to bind to other sarcomeric proteins, being the main reason for the development of hypertrophic cardiomyopathy in both pediatric and adult populations [ 44 , 45 ]. To date, this specific MYBPC3 c.1224-52 G>A (IVS13-52 G>A) variant has only been identified in adult patients with hypertrophic cardiomyopathy containing a heterozygous variant or unknown heterozygosity [ 17 , 18 , 19 , 20 , 21 ] (summarized in Table 3 ). This specific truncation occurs in the immunoglobulin-type C2 domain, which forms a compact globular structure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Around 75% of these variants were found to be loss-of-function and resulted in absent or truncated proteins with impaired ability to bind to other sarcomeric proteins, being the main reason for the development of hypertrophic cardiomyopathy in both pediatric and adult populations [ 44 , 45 ]. To date, this specific MYBPC3 c.1224-52 G>A (IVS13-52 G>A) variant has only been identified in adult patients with hypertrophic cardiomyopathy containing a heterozygous variant or unknown heterozygosity [ 17 , 18 , 19 , 20 , 21 ] (summarized in Table 3 ). This specific truncation occurs in the immunoglobulin-type C2 domain, which forms a compact globular structure.…”
Section: Discussionmentioning
confidence: 99%
“…Intronic variants in MYBPC3 in the context of hypertrophic cardiomyopathy have also been identified [ 14 , 15 , 16 ] and, in the last few years, have focused on one specific intronic MYBPC3 variant c.1224-52G>A (IVS13-52G>A) [ 17 , 18 , 19 , 20 , 21 ]. Specifically, Bagnall et al reported on a cohort of unrelated gene-elusive probands with HCM that had undergone genome sequencing, in which they identified the intronic MYBPC3 variant c.1224-52G>A in two adult male family members, as well as an adult proband from another family [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…RNA analyses were performed to confirm aberrant splicing through the inclusion of cryptic exons in cardiomyocytes from patient-derived induced pluripotent stem cells (iPSC-CMs) and in a myectomy sample from one affected relative of the proband (c.1928−569G > T only). In addition, the role of one MYBPC3 intronic variant (c.3331−26T > G) was found to account for a genotype-negative proband in a family with a history of HCM ( 71 ). This variant segregates with two diseased descendants of the proband and it was found in unrelated HCM patients.…”
Section: Cardiomyopathy-associated Genetic Variants At Deep Intronic ...mentioning
confidence: 99%
“…Currently, the common method for gene sequencing is next-generation sequencing (NGS), but most of the gene panels and exome assays are targeted to coding regions and canonical splice sites, whereas introns and promoter regions are ignored. On the other hand, there is increasing evidence that variants in non-coding regions can contribute to the disease, mostly by altering splicing [ 4 , 5 , 6 , 7 , 8 , 9 ]. A whole-gene sequence is usually obtained only by whole-genome sequencing, which is more expensive than target gene analysis.…”
Section: Introductionmentioning
confidence: 99%